Elements that affect compliance among smallholders toward RSPO at Kundang Ulu, Ledang, Johor / Siti Khuzaimah Muhamad Nazri - Muhamad Nazri, Siti Khuzaimah (Faculty of Plantation and Agrotechnology, 2017)
Smallholders nowadays need to certify with RSPO to have sustainable practices. High numbers of Smallholders are uncertified with the RSPO. The objectives of this study are; (1) to study the elements that affect the compliance toward RSPO. (2) To identify the relationship between elements that effect compliance toward RSPO. (3) To determine the most dominant elements to compliance towards RSPO. Primary data with structured questionnaires were collected from the 132 respondents of smallholder from 200 populations. The questionnaire was consisting into three parts which are Part A for Respondents profile, Part B for independent variable and Part C is dependent variable. The data collected then interpreted by using the descriptive analysis, reliability analysis, Spearman correlation and multiple regressions. The result for reliability test is more than 0.7 and the questionnaires are reliable and accepted. The data analysis resulted from Spearman Correlation which is practice; environment, attitude and knowledge have a significant and moderate positive relationship to compliance toward RSPO. The regression is used to analyze the influence of the independent variable, X (practice, environment, attitude and knowledge) on the dependent variable, Y (compliance). Result from both studies, attitude showed that it is the highest elements among of others while practice is the lowest elements among others.